Effects of Breeder Age on Genetic Parameter Estimates of Slaughter and Carcass Traits in Japanese Quail (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aimed to determine the phenotypic values of the slaughter and carcass traits in the flocks of quails obtained when a flock of parent quails were at 12, 16, and 20 weeks of age and to estimate the heritabilities and the genetic correlations for these traits. For this purpose, a total of 1,346 Japanese quails were slaughtered at 8 weeks of age, and their slaughter weights as well as carcass, breast, leg, and abdominal fat weights and ratios were determined. Differences in all traits were detected between female and male quails (P<0.05). The averages of many important traits, primarily slaughter weight, carcass weight, and breast weight, increased with the increase in the breeder age. On the contrary, the carcass yield decreased (P<0.05). There were no significant variations in the phenotypic and genetic variances for the slaughter and carcass traits in the flocks obtained when the breeder flock was at different ages. The heritabilities for slaughter weight, carcass weight, and abdominal fat weight were estimated to be moderate, and the genetic correlations among them were estimated to be positive and high. In conclusion, it is possible to state that positive results might be obtained by using the carcass ratio as the criterion for selection in quails. Besides, the breeder age was discovered to have had no significant effect on the genetic parameter estimations.